Learning to Write Scientific Articles with The Project Based Learning on The Levels of Students’ Creative Thinking - Haekal, Muhammad Husain; Zulaeha, Ida (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
The students? skills of writing scientific articles are necessarily acquired in order to put the students? ideas into writings, within appropriate methods and styles. The learning process of writing scientific articles is suitably acquired with the project based learning which assesses the levels of students? creative thinking. The research aims to explain aims to explain the effectiveness of learning process in writing scientific articles with the project based learning and the levels of students? creative thinking. The research applied quasi experiment. The data were collected using purposive sampling method. The data were analyzed using validity and reliability tests. The sample were analyzed using normality and homogeneity tests. Finally, the data were analyzed using paired t-test. All of them were analyzed using paired t-test. All the tests used SPSS 25 test program the results of the research were concluded by applying the project based learning and the levels of students? creative thinking on students? writing practices. The results found that learning to write scientific articles using the project based learning effectively affect students with a high level of creative thinking that those with medium and low levels. The benefits of this research were to enrich the thesaurus theory of learning to write scientific articles based on the level of students? creative thinking more effectively.